The beneficial effects of aerobic and concurrent training on metabolic profile and body composition after detraining: A 1-year follow-up in postmenopausal women - Rossi, F. E. [UNESP]; Diniz, T. A.; Neves, L. M.; Fortaleza, A. C.S. [UNESP]; Gerosa-Neto, J. [UNESP]; Inoue, D. S. [UNESP]; Buonani, C. [UNESP]; Cholewa, J. M.; Lira, F. S. [UNESP]; Freitas, I. F. [UNESP] (Springer Nature, 2017)
Background/Objectives:Aerobic and concurrent training (CT, aerobic and strength training) improves body composition and metabolic profile; however, it is not known whether these positive outcomes acquired after aerobic or CT are maintained long term (≥6 months) after program interruption in postmenopausal women. This study investigated the changes in total and appendicular body composition, bone mineral density and metabolic profile following 16 weeks of aerobic or CT, and through 6 months and 1 year of detraining in postmenopausal women.Subjects/Methods:In total, 60 postmenopausal women were divided into the following groups: Aerobic (AT), aerobic plus strength training (CT) and control group (CG), and 31 participants were assessed for the 1 year follow-up. Body composition and bone mineral density were evaluated by dual-energy X-ray absorptiometry (DXA), and total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, triacylglycerol, glucose, insulin, leptin, adiponectin and plasminogen activator inhibitor-1 (PAI-1) were assessed.Results:There were main effects of time for arm fat mass, arm lean mass and trunk lean mass (P<0.05). There was a statistical difference between AT and CG for leg fat mass and percentage of fat (P<0.05). After 6 months of detraining, leg lean mass decreased in relation to post-intervention, and there was a statistically significant interaction for total and appendicular lean mass (P<0.05). There were differences between CT and CG in glucose and between AT and CG in glucose and triacylglycerol (P<0.05).Conclusions:A duration of 16 weeks of aerobic or CT improved total and appendicular body composition and metabolic profile but after 6 months of detraining, leg lean mass returned to the values obtained pre-training in CT.